Human-induced threats to wildlife in developing regions (Zoological Records and Reviews, 2024)
Wildlife in developing regions faces an accelerating suite of human-induced threats that are structurally distinct fromthose documented in industrialised nations, including subsistence and commercial bushmeat hunting, unregulatedsmall-scale mining, agricultural frontier expansion, live wildlife trade, and zoonotic disease spillover amplified byhuman-wildlife interface density. This study quantifies the relative importance and spatial distribution of five threatcategories across three biodiversity-rich developing regions -- West Africa (Ghana, Cameroon), South and SoutheastAsia (Cambodia, Myanmar), and Amazonian South America (Peru, Bolivia) -- using camera trap surveys (n = 312stations, 84,621 trap-nights), community interview-based threat perception surveys (n = 1,847 households), NDVI-baseddeforestation rate analysis, and TRAFFIC wildlife trade seizure data (2018-2023). Deforestation rate was the strongestpredictor of large mammal occupancy decline across all three regions (mean beta = -0.68 +- 0.09 per 10% forest coverloss; GLMM p < 0.001). Bushmeat hunting pressure index was negatively correlated with medium and large mammalcamera trap rates (r = -0.74, p < 0.001) and showed no significant trend improvement over the five-year study period inWest Africa or Southeast Asia. Live wildlife trade seizure data revealed that reptiles and passerine birds constituted64.8% of confiscated individuals across all three regions. Community surveys identified poverty and lack of livelihoodalternatives as the primary drivers of hunting and forest clearing, with 78.4% of households reporting willingness to adoptalternative livelihoods if economically viable options were available. These findings provide a comparative baseline fordesigning integrated conservation and development interventions aligned with IUCN Category VI protected areamanagement and CITES implementation frameworks.
Keywords: community conservation; Amazonia; Southeast Asia; West Africa; large mammal decline; camera traps; developing regions; wildlife trade; deforestation; bushmeat hunting